Pelatihan Tentang Kondisi Fisik Cabang Olahraga Bolavoli pada Mahasiswa Pendidikan Jasmani - Zaim Zen, Muhammad; Setyawan, Risfandi; Wahyu Sulistyo, Yully (UIR Press, 2024)
The community service activities carried out have the aim that students have an understanding and knowledge related to the components of physical conditions and how to form training in volleyball, in the game of volleyball physical conditions as the main support for everyone in playing volleyball because it will have a positive impact on everyone to get good achievements, in the implementation of this activity using lecture, question and answer methods and demonstrations and practice, for this reason the implementation of this service students will get an explanation of material about physical conditions in volleyball which consists of endurance, strength, speed, agility, and explosive power. Every implementation of service activities there is an evaluation with the aim of being able to summarise related to the activity situation and also the suggestions obtained from the activity, in the results of this service activity with an increased understanding of students related to the physical condition material of volleyball that has been explained. For this reason, it can be concluded that the explanation of the physical condition material has a positive impact on a student's understanding and knowledge in the sport of volleyball.